(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Theoretical Framework: This study addressed the phenomenon of quiet quitting as a behavior manifested in employees performing only the minimum required work without showing additional commitment or initiative. This phenomenon is linked to causes such as burnout, lack of appreciation, and the absence of career advancement opportunities, making it a direct threat to employee engagement and organizational performance stability. The study aimed to explore the relationship between the dimensions of digital leadership and the dimensions of quiet quitting among the employees of Al-Maram Advertising Company. Objective: The study aimed to test the hypotheses regarding the relationship and impact between the dimensions of digital leadership — namely (digital leaders’ competence, digital leaders’ capability, organizational structure, and organizational strategy) — and the dimensions of quiet quitting — represented by (work overload, unfair compensation, poor work environment, and lack of career advancement opportunities). It also sought to analyze how digital leadership contributes to reducing levels of quiet quitting. Methodology: The study employed a quantitative analysis based on questionnaires distributed to employees of Al-Maram Advertising Company, with data collected from 48 employees in addition to interviews with senior and middle management. A structural model was designed to illustrate the direct effects of each digital leadership dimension on quiet quitting. Findings: The study revealed a statistically significant inverse relationship between all dimensions of digital leadership (competence, capability, structure, and strategy) and manifestations of quiet quitting among Al-Maram employees. Collectively, digital leadership accounted for 92% of the variance in quiet quitting (R² = 0.922), with digital leaders’ competence having the strongest effect (β = -0.755). While the contributions of the other dimensions were smaller, they remained statistically significant. The results confirm that enhancing digital leadership practices effectively reduces the likelihood of employees’ psychological withdrawal. Recommendations: The study recommended that Al-Maram Advertising Company focus on improving digital leaders’ competence through specialized training programs in digital leadership, and activates clear strategies for leveraging technology in communication and motivation. It also advised restructuring the work environment to align with digital transformation requirements. Moreover, the study recommended developing clear promotion and recognition policies to ensure employee motivation and reduce the likelihood of quiet quitting, thereby enhancing employee engagement and sustaining the company’s high performance.